Deformability of the pulsating left ventricular wall: A new aspect elucidated by high resolution ultrasonic methods - Tanaka, Motonao; Sakamoto, Tsuguya; Sugawara, Shigeo; Katahira, Yoshiaki; Hasegawa, Kaoru; Nakajima, Hiroyuki; Kurokawa, Takafumi; Kanai, Hiroshi; Hasegawa, Hideyuki (Journal of cardiology, 2017)
Although the deformability of the left ventricular (LV) wall appears to be important in maintaining effective cardiac performance, this has not been debated by anyone, probably owing to the difficulties of the investigation. This study applies a new technology to demonstrate how the LV wall deforms so as to adjust for optimum cardiac performance. Ten healthy volunteers were the subjects. Using echo-dynamography, an analysis at the “microscopic” (muscle fiber) level was done by measuring the myocardial axial strain rate (aSR), while the “macroscopic” (muscle layer) level contraction-relaxation/extension (C-R/E) properties of the LV wall were analyzed using high frame rate 2D echocardiography. Deformability of the LV was classified into three types depending on the non-uniformity of both the C-R/E properties and the aSR distribution. “Basic” deformation (macroscopic): The apical posterior wall (PW) thickness change was concentric and monophasic, whereas it was eccentric and biphasic in the basal part. This deformation was large in the PW, but small in the interventricular septum (IVS). The elongation of the mitral ring diameter and the downward movement of its posterior part were shown to be concomitant with the anterior extrusion of the PW. “Combined” deformation (macroscopic and microscopic): This was observed when the basic deformation was coupled with the spatial aSR distribution. Three patterns were observed: (a) peristaltic; (b) bellows-like; and (c) pouch-like. “Integrated” deformation: This was the time serial aSR distribution coupled with the combined deformation, illustrating the rotary pump-like function. The deformability of the LV assigned to the apical part the control of pressure and to the basal part, flow volume. The IVS and the PW exhibited independent behavior. The non-uniformity of both the aSR distribution and the macroscopic C-R/E property were the basic determinants of LV deformation. The apical and basal deformability was shared in LV mechanical function.